FUNGSI LURAH DALAM MENYELENGGARAKAN KETENTRAMAN DAN KETERTIBAN UMUM DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Wan Indrawan; isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study titled Function headman In Peace Organizing and Public Order In New Simpang Village Subdistrict Handsome Pekanbaru. The problem in this research is how the headman Function In Hold Public Peace and Order in the New District of Handsome Simpang Village Pekanbaru. This includes research into the type of qualitative research that provides a descriptive overview of the headman Function In Hold Public Peace and Order in the New District of Handsome Simpang Village Pekanbaru. Based on the description that has been described previously, it can be concluded that the function of village chief in the implementation of peace and order in the Village District of New Simpang Handsome Pekanbaru already well underway. Keywords: Function headman, Peace and Public Order